(untitled) (Global Journal of Human-Social Science, 2013)
A national theatre embodies the performing treasures of the nation’s inheritance for a glorious cause. The theatre brings the best not just to its people but also to the world and further deals with artistic and creative imaginations. It then beholds on Government to encourage the theatre as a body that preserves and promotes the cultural values of the nation. As a cultural Institution, this study explores the management constraints on the National Arts Theatre as well as that of the MUSON Centre, Lagos. Personal Observation and interview techniques were adopted. At the end, it was observed that government policies, funding and organisational bottle-neck that encourages bureaucracy are some major challenges against effective management of a theatre in a developing country.